Increasing the use of medical rehabilitation by children and adolescents with migrant background through a multimodal information campaign: protocol of a trend study and accompanying process evaluation (MiMi-Reha-Kids, DRKS00019090) - Banaschak, Hannes; Bartolini, Flaminia; Salman, Ramazan; Bethge, Matthias (Frontiers in Public Health, 2023)
Background: Chronic illnesses can have an unfavorable impact on the participation opportunities of children and adolescents. The German health care system offers medical rehabilitation in order to prevent negative effects, however, migrant children and adolescents make use of this option less frequently than their peers without a migrant background. A multimodal information campaign was developed to increase the use of medical rehabilitation by children and adolescents with a migrant background, and to reduce disparities in health care. Methods: The process evaluation will examine the implementation of a multimodal information campaign intended to increase the use of medical rehabilitation by migrant children and adolescents. The information campaign follows a low-threshold participatory approach. In a first step, persons from different migrant communities in Berlin and Hamburg are trained to become transcultural health mediators. These mediators then share their knowledge about chronic illnesses and medical rehabilitation with other families at information events held in their native language. The transcultural mediators also support migrant families in applying for medical rehabilitation. The effectiveness of the intervention will be tested by a trend study with repeated cross-sectional surveys. For this purpose, all families in the project regions of Berlin and Hamburg whose child has received medical rehabilitation are surveyed annually in order to be able to map changes in the proportions of children and adolescents with a migrant background over the course of the project. Discussion: The study protocol describes a complex intervention to increase the use of medical rehabilitation by migrant children and adolescents, and the accompanying process evaluation and trend study. The intervention is intended to contribute to reducing health inequalities in Germany. Conclusion: The study described in this protocol will provide extensive data on the multimodal information campaign and can thus help organizations and institutions adapt or further develop similar measures for other regions